CHANGE DETECTION OF CORAL REEF HABITAT USING LANDSAT IMAGERY IN MOROTAI ISLAND NORTH MALUKU PROVINCE - Nurhalis Wahiddin; Vincentius P Siregar; Bisman Nababan; Indra Jaya; Sam Wouthuyzen (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
ABSTRACT Scientific information on coral reef habitat changes of Morotai island is very limited to none. This study aimed to detect the change of coral reef habitats between 1996 and 2013, using Landsat imagery integrated with field data in 2012. The research was conducted in the coral reef ecosystem of Morotai Island in North Maluku province. Change detection analyses were conducted using supervised classifications and transformation depth invariant index (DII), with five habitat classes i.e., mixed-habitat, coral, seagrass, sand, and rubble. The result showed that in 1996-2002 there was a significant increase in the mix-habitat and rubble classes (11.3% and 32.5%), however,  there  was  a siginifcant decrease in the sand, seagrass, and coral classes of -14.1%, -14.9%, and -16.6%, respectively. In 2002-2013, mixed-habitat, sand, and seagrass classes were increase by 1.1%, 13.3%, and 24.78%, respectively.  Meanwhile, coral and rubble classes were decrease by -22.7% and -27.0%, respectively. Within the period of 1996-2013, there was about 43.6% loss of coral reef of Morotai island.  This was probably caused by the increase of seas surface temperature nad and the increase of human activities in the region. Keywords: coral reef habitats, Landsat, change detection, Morotai Island